Concise handbook of waste treatment technologies - Arni, Saleh Al; Elwaheidi, Mahmoud (Boca Raton, FL : CRC Press, 2021)
"With specialized and succinct coverage, this book provides readers with an integrated overview of various waste treatment technologies and related issues. Instead of dealing separately with each type of waste material, the book summarizes important waste treatments from a holistic perspective. This guidebook is written for early career professionals, non-specialists, and specialists seeking to understand waste and its proper management and disposal techniques"--
8.2.2 Leachate Calculation -- 8.2.3 Landfill Hydrology Model -- 8.3 Composting -- 8.3.1 Factors Controlling Composting Process -- 8.3.1.1 Temperature -- 8.3.1.2 Moisture Content -- 8.3.1.3 Carbon/Nitrogen (C/N) Ratio -- 8.3.1.4 Particle Size -- 8.3.1.5 Aeration -- 8.3.2 Methods of Composting -- 8.4 Physical-Biological Processes -- References -- 9 Waste Disposal by Thermal Processes -- Key Learning Objective -- 9.1 Introduction -- 9.2 Incineration -- 9.3 Pyrolysis -- 9.4 Gasification -- References -- 10 Industrial Wastewater Treatment -- Key Learning Objectives -- 10.1 Introduction
OCLC-licensed vendor bibliographic record.
Keywords: Sanitary engineering; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY / Engineering / Chemical & Biochemical